2018
DOI: 10.1016/j.annepidem.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Childhood body size and midlife mammographic breast density in foreign-born and U.S.-born women in New York City

Abstract: Heavy childhood body size is associated with lower mammographic density, consistent with its associations with breast cancer risk. Suggestive findings by nativity require confirmation in larger samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Our findings of strong positive associations between body fatness measures and adipose tissue are consistent with those from previous studies of PMD (13,17,18,(34)(35)(36)(37)(38). Including our previous report from the NHS and NHSII (18), studies have consistently reported that higher levels of body fatness are associated with lower levels of PMD, indicating higher amount of non-dense (adipose) tissue compared with that of dense tissue (epithelial and fibrous stromal tissues combined).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings of strong positive associations between body fatness measures and adipose tissue are consistent with those from previous studies of PMD (13,17,18,(34)(35)(36)(37)(38). Including our previous report from the NHS and NHSII (18), studies have consistently reported that higher levels of body fatness are associated with lower levels of PMD, indicating higher amount of non-dense (adipose) tissue compared with that of dense tissue (epithelial and fibrous stromal tissues combined).…”
Section: Discussionsupporting
confidence: 90%
“…A recent systematic review concluded there was a likely association between childhood animal protein intake and earlier puberty assessed by age at menarche and age at peak height velocity (23). Finally the heaviest body size at age 10 as illustrated using the Stunkard images vs. the leanest body sized girls had a 5.9 fold (95% CI: −9.2-2.3) lower percent breast density when they reached ages 40-64 years, with 7.69 cm 2 (95% CI: −13.9-0.63) smaller dense breast area, and 26.17 cm 2 (95% CI: 9.42-43.58) larger non-dense area (24).…”
Section: The First D: Windows Of Exposure Across the Life Course (Figmentioning
confidence: 97%